The Study of Legal Aspects of Construction In Civil Building - Janizar, Syapril; Anisarida, An An (Greenation International Journal of Law and Social Sciences, 2023)
Development is very beneficial for human life, but it does not escape losses both material losses and casualties if it is not built properly. One of them is the collapse of the Kutai Kartanegara Bridge which caused people to die and be injured. Building failure is one of the consequences that can endanger public safety and state losses. The failure of this building is explicitly regulated in Law Number 2 of 2017 concerning Construction Services starting from Article 60 to Article 67. In addition, building failure is regulated in Government Regulation Number 29 of 2000 concerning the Implementation of Construction Services, namely in Chapter V Articles 34 to Article 48. Criminal liability under the Construction Services Law can only be imposed on individuals who directly carry out construction work and not on construction service providers in the form of corporations because to fund the corporation requires clarity to whom sanctions will be imposed. Based on the results of the analysis that based on the theory of criminal liability, with the shift of legal subjects from fysieke dader to functionale dader, corporations can be held accountable. This is also supported by theories and doctrines about corporate responsibility. With the birth of Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations, where this is intended as an effort to provide legal certainty and encourage the effectiveness and optimization of procedural law in handling criminal cases with corporate actors and / or corporate administrators.